Mechanical behaviour of acrylonitrile butadiene styrene (ABS) specimen by fused deposition modelling (FDM) - Selvamani, Sathish Kumar (2019)
Fused deposition modelling (FDM) is a prominent additive manufacturing technology that has various impactful contribution in numerous sectors when associated with ABS. Applications of ABS in FDM can be benefited in fabrication of models, prototypes, patterns and tools. Adding to that, it is very suitable for applications where strength, ductility, machinability and thermal stability are required. Simultaneously, there is still room for improvement to overcome the downsides found in this technology. Lack of information on the influence of infill percentage and raster angle combination, in the wide mechanical properties of ABS based low cost FDM machine specimens is one of the identified research gap. Thus, to coincide with the research gap, three objectives were set. The objectives were to develop ABS testing specimens by varying its’ infill percentage and raster angle using FDM technique, to investigate the prepared ABS specimens’ mechanical properties by performing tensile test, compression test, bending test and impact test and to develop an optimized printing parameter combination using statistical analysis. Hence, this research work comprises of printing test specimens using specific standards according to test conducted and implementation of mechanical characterization which includes tensile test, bending test, compression test and impact test of specimens printed with altered infill percentage and raster angle which were the selected varying printing parameters. Thorough analysis comprising experimental data evaluation, statistical evaluation and optimizations using response surface methodology were carried out to study in detail the effect of the selected printing parameters on the mechanical property of the ABS-based specimens. Outcome of mechanical test shows, the infill percentage demonstrates significant effect on all the mechanical properties tested. For instance, higher the infill percentage, the higher the value of the properties. Meanwhile raster angle has varying effects with properties tested. For tensile test, highest elastic modulus and ultimate tensile strength achieved with raster angle of 0° whereas highest yield strength (0.2% offset) was achieved with raster angle of 45°. For bending test, raster angle of 0° shows that it has important effect on the flexural properties since the highest value for properties were achieved at this raster angle. For compression test, the highest value for both compression strength and compression modulus were achieved when it is at 90° raster angle. For impact test, raster angle of 45° has the highest effect on the impact properties since the impact properties with this 45° raster angle achieved the highest value. Furthermore, completed optimization suggests the parameter for each test that would result in overall optimum mechanical properties and optimum individual mechanical properties. Parameters for optimum tensile properties and compression properties are 90° raster angle and 99% infill percentage. Meanwhile, parameter for optimum bending properties are 0° raster angle and 99% infill percentage. Finally, parameter for optimum impact properties are 52.27° raster angle and 99% infill percentage. Overall results of this research show that infill percentage has linear relationship with all the mechanical properties whereas raster angle has varying effect on the mechanical property of the specimens and it was proved by the validation of the experimental data using statistical evaluations. As a recommendation, parameters such as layer thickness, air gap and contour width also can be varied with infill percentage and raster angle to identify detailed effect of printing parameters on the mechanical property of printed specimens for the future improvement of the strength of the ABS based FDM specimens or products.